1977
DOI: 10.1136/ard.36.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid in England and Scotland.

Abstract: SUMMARY Serum uric acid (SUA) was measured in 512 men and 254 women from two English regions and in 337 men from one Scottish region. Mean SUA levels were the same in the men (5-5 mg/100 ml) and similar in the women (3-9 and 4-1 mg/100 ml). The apparent rarity of gout in Scotsmen cannot be explained by regional differences in SUA levels or in the prevalence of hyperuricaemia (defined as SUA of 7.0 mg/100 ml or over) which was present in 6.6% of the English men and 8 of the Scots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
6

Year Published

1978
1978
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
5
19
0
6
Order By: Relevance
“…These rates are 2–4 times higher than those described for the general ‘healthy’ Arab [5] or Caucasian populations [3,4]. Gender (male sex), obesity (as assessed with BMI) and diabetes were significant determinants of whether or not an individual would have hyperuricemia, even after adjustment for potential confounding.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These rates are 2–4 times higher than those described for the general ‘healthy’ Arab [5] or Caucasian populations [3,4]. Gender (male sex), obesity (as assessed with BMI) and diabetes were significant determinants of whether or not an individual would have hyperuricemia, even after adjustment for potential confounding.…”
Section: Discussionmentioning
confidence: 65%
“…The worldwide prevalence of hyperuricemia is high, with reported rates of 35.1% (men) and 8.7% (women) in the Seychelles [1], 10.6% in Thailand [2], 7.2% (men) and 0.04% (women) in England and Scotland [3], 11.2% in the USA [4] and 8.4% in Saudi Arabia [5]. The putative associations of hyperuricemia in these populations include age, gender, smoking, alcohol consumption and lifestyle, which in themselves are also risk factors for CAD and stroke [6], among other variables, also seen at high frequencies in individuals with hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…The purine-rich nature of muscle tissue suggests one reason why this variable might be implicated, although the correlation between SUA and muscle size (r = 0.237, P = 0.001) disappeared when correlated for BMI (r = 0-010, P = 0.86). Sturge et al (1977) reported that lean body mass (LBM) was positively correlated with SUA in both sexes, but when entered into step-wise regression together with a measure of total body mass (ponderal index) LBM in males no longer explained a significant amount of SUA variation. A correlation between SUA and LBM (t55 = 6.34 P<0.001) has been reported by Kennedy et al (1975); this result is based on a pooled group of 27 males and 30 females and a sex difference in the effect of LBM on SUA is not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently non-genetic factors are associated with plasma, serum and urine uric acid levels. They include nutrition such as nucleic acid, purines and protein (Waslien et al, 1968;Clifford et al, 1976;Seegmiller et al, 1963;Rauch-Janssen et al, 1977), alcohol consumption (Lieber et aI., 1962;Brooks and Mueller, 1966;Saker et al, 1967;Gulbrandsen et al, 1979), body weight, obesity or body surface (Dunn et aI., 1963;Brooks and Mueller, 1966;Sturge et al, 1977;Noppa et al, 1978;O'Brien et al, 1966), social status or occupation (Dunn et al, 1963;Montoye et aI., 1967), and education (Dunn et al, 1963).…”
Section: Introductionmentioning
confidence: 99%